Towards greater flexibility in the learning ecosystem - promises and obstacles of service composition for learning environments - Chang, Vanessa; Guetl, Christian; Wurzinger, G. (IEEE Industrial Electronics Society, 2009)
Today's knowledge society of the 21st century requires a flexible learning environment which is capable to adapt according to teaching and learning objectives, students profiles and preferences for information and communication technologies and services. To combine tasks and context dependent services to a tailored ad-hoc learning environment, service orchestration and choreography are promising and interesting concepts. In this paper, backed by an ecosystem-based conceptual architecture, SOAP-based and lightweight Web service technologies for service composition, will be reviewed, and the promises and challengs for both approaches will be discussed. Based on these findings our motivation for a light-weight web services composition is given and a first approach is outlined which builds on the combination of machine-redeable service description, mechanism of tool-assisted mashup creation and standardizes languages for service composition.